Policy scorecard for gender mainstreaming: gender equity in health policy - Helen Keleher (Elsevier, 2013)
Abstract Objectives : To examine whether gender mainstreaming for women's health is included in national and state health policies. Methods : A policy analysis tool (Policy Scorecard) was developed and then applied to Australia's National Health Priority Areas as well as policies of three Australian States. Results : Despite Australia's leadership in women's health policy, its health policies are largely devoid of gender equity concerns at both national and state levels. Mainstreaming of gender equity outcomes has not yet occurred in Australia. Conclusions : Applying the Policy Scorecard for Gender Mainstreaming to local and country‐specific policies is revealing of governments' commitment to women, and how well gender equity goals are embedded into policies and programs. Policy analysis using this gender‐sensitive Policy Scorecard provides opportunities for advocacy to advance women's health and gender equity at any level of government, in any country.